MicroRNA-153 impairs presynaptic plasticity by blocking vesicle release following chronic brain hypoperfusion - Yan, Mei-Ling (Cell Commun Signal, 2020)
BACKGROUND: Chronic brain hypoperfusion (CBH) is closely related to Alzheimer’s disease (AD) and vascular dementia (VaD). Meanwhile, synaptic pathology plays a prominent role in the initial stage of AD and VaD. However, whether and how CBH impairs presynaptic plasticity is currently unclear. METHODS: In the present study, we performed a battery of techniques, including primary neuronal culture, patch clamp, stereotaxic injection of the lentiviral vectors, morris water maze (MWM), dual luciferase reporter assay, FM1–43 fluorescence dye evaluation, qRT-PCR and western blot, to investigate the regulatory effect of miR-153 on hippocampal synaptic vesicle release both in vivo and in vitro. The CBH rat model was generated by bilateral common carotid artery ligation (2VO). RESULTS: Compared to sham rats, 2VO rats presented decreased field excitatory postsynaptic potential (fEPSP) amplitude and increased paired-pulse ratios (PPRs) in the CA3-CA1 pathway, as well as significantly decreased expression of multiple vesicle fusion-related proteins, including SNAP-25, VAMP-2, syntaxin-1A and synaptotagmin-1, in the hippocampi. The levels of microRNA-153 (miR-153) were upregulated in the hippocampi of rats following 2VO surgery, and in the plasma of dementia patients. The expression of the vesicle fusion-related proteins affected by 2VO was inhibited by miR-153, elevated by miR-153 inhibition, and unchanged by binding-site mutation or miR masks. FM1–43 fluorescence images showed that miR-153 blunted vesicle exocytosis, but this effect was prevented by either 2′-O-methyl antisense oligoribonucleotides to miR-153 (AMO-153) and miR-masking of the miR-153 binding site in the 3′ untranslated region (3’UTR) of the Snap25, Vamp2, Stx1a and Syt1 genes. Overexpression of miR-153 by lentiviral vector-mediated miR-153 mimics (lenti-pre-miR-153) decreased the fEPSP amplitude and elevated the PPR in the rat hippocampus, whereas overexpression of the antisense molecule (lenti-AMO-153) reversed these changes triggered by 2VO. Furthermore, lenti-AMO-153 attenuated the cognitive decline of 2VO rats. CONCLUSIONS: Overexpression of miR-153 controls CBH-induced presynaptic vesicle release impairment by posttranscriptionally regulating the expression of four vesicle release-related proteins by targeting the 3’UTRs of the Stx1a, Snap25, Vamp2 and Syt1 genes. These findings identify a novel mechanism of presynaptic plasticity impairment during CBH, which may be a new drug target for prevention or treatment of AD and VaD. GRAPHICAL ABSTRACT: [Image: see text]